Opportunity to study and analysis of traction abnormal mode electrical complex mine electric using the machine petri nets - Sinchuk, O. N.; Chernaja, V. O.; Budnikov, V. N. (НТУ "ХПИ", 2013)
The paper deals with the use of the apparatus for the study of Petri nets psevdoavariynyh modes of operation of electrical traction systems miner-axle locomotives. Models of traction electrical complex with protection switching converters from emergency situations.

В статье рассмотрены вопросы использования аппарата сетей Петри для изучения псевдоаварийных режимов функционирования тяговых электротехнических комплексов рудничных двухосных электровозов. Представлены модели тягового элек- тротехнического комплекса с защитой импульсных преобразователей от аварийных ситуаций.